Synthesis of chromen-4-one-oxadiazole substituted analogs as potent β-glucuronidase inhibitors - Taha, Muhammad; Rahim, Faizal; Ali, Muhammad; Khan, Muhammad Naseem; Alqahtani, Mohammed A.; Bamarouf, Yasser A.; Gollapalli, Mohammed; Farooq, Rai Khalid; Ali Shah, Syed Adnan; Ahmed, Qamar Uddin; Zakaria, Zainul Amiruddin (MDPI, 2019)
Chromen-4-one substituted oxadiazole analogs 1–19 have been synthesized, characterized and evaluated for β-glucuronidase inhibition. All analogs exhibited a variable degree of β-glucuronidase inhibitory activity with IC50 values ranging in between 0.8 ± 0.1–42.3 ± 0.8 µM when compared with the standard d-saccharic acid 1,4 lactone (IC50 = 48.1 ± 1.2 µM). Structure activity relationship has been established for all compounds. Molecular docking studies were performed to predict the binding interaction of the compounds with the active site of enzyme.